2019
DOI: 10.1007/s13595-019-0807-1
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-tactile and topographic characterizations of finished wood surface quality by French consumers and industrials: acceptability thresholds for raised grain

Abstract: & Key message Raised grain occurring on wood surfaces after the application of a waterborne varnish was felt by human touch because of protruding peaks and a certain amount of materials in the core of the roughness profile. This tactile sensation was correlated with specific roughness parameters. Characteristics of a finished surface quality that is acceptable to consumers were determined. & Context Raised grain occurs on wood surfaces after the application of a waterborne varnish and forces manufacturers to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, there is also evidence that the use of wood in housing construction affects homeowners' perceptions of their identities (Ridoutt et al 2005). Especially with respect to the visual and tactile properties of wood, it has been found that consumers prefer smooth surfaces in particular (De Morais and Pereira 2015;Ramanakoto et al 2017;Ramanakoto et al 2019), and that by using vision and touch they are capable of distin-guishing natural wood from artificial materials (Overlievt and Soto-Faraco 2011). Yet, although consumers have been found to appreciate the naturalness of wood in the home environment (Jonsson et al 2008;Nyrud and Bringslimark 2010;Bhatta et al 2017;Moresová et al 2019), this does not necessarily lead to sustainable purchasing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is also evidence that the use of wood in housing construction affects homeowners' perceptions of their identities (Ridoutt et al 2005). Especially with respect to the visual and tactile properties of wood, it has been found that consumers prefer smooth surfaces in particular (De Morais and Pereira 2015;Ramanakoto et al 2017;Ramanakoto et al 2019), and that by using vision and touch they are capable of distin-guishing natural wood from artificial materials (Overlievt and Soto-Faraco 2011). Yet, although consumers have been found to appreciate the naturalness of wood in the home environment (Jonsson et al 2008;Nyrud and Bringslimark 2010;Bhatta et al 2017;Moresová et al 2019), this does not necessarily lead to sustainable purchasing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the results, consumers preferred a homogeneous visual appearance and moderate color intensity in the case of wooden deck materials (Nyrud et al, 2008); furthermore, they preferred wood with fewer knots over wood with many knots (Nyrud & Bringslimark, 2010). Tactile properties, such as smoothness (Berger et al, 2006;Bhatta et al, 2017;Jonsson et al, 2008;Lindberg et al, 2013;De Morais & Pereira, 2015;Ramanakoto et al, 2019), roughness (Bhatta et al, 2017;Lindberg et al, 2013;De Morais & Pereira, 2015), and vibration (Negreira et al, 2015;Viholainen et al, 2020) were identified. Several studies concluded that consumers preferred smooth surfaces (Bhatta et al, 2017;De Morais & Pereira, 2015;Ramanakoto et al, 2019), and wood was seen as a soft and warm material (Strobel et al, 2017;Viholainen et al, 2020).…”
Section: Sensory Dimensionmentioning
confidence: 99%